2010
DOI: 10.1261/rna.2158410
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the three-way helical junction of the hepatitis C virus IRES element

Abstract: The hepatitis C virus internal ribosome entry site (IRES) element contains a three-way junction that is important in the overall RNA conformation, and for its role in the internal initiation of translation. The junction also illustrates some important conformational principles in the folding of three-way helical junctions. It is formally a 3HS 4 junction, with the possibility of two alternative stacking conformers. However, in principle, the junction can also undergo two steps of branch migration that would fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 55 publications
2
25
0
Order By: Relevance
“…Helices at a 2-way junction can therefore remain collinear even though no significant electrostatic repulsions exist between them. Moreover, at a 3-helix junction, the collinearity of two helices due to coaxial stacking implicitly means that a plane is formed with the third (Kim et al 2002;Mikulecky et al 2004;Mohanty et al 2005;Ouellet et al 2010). Some 4-helix junctions have also been shown to have relatively planar structures (Lilley 1998(Lilley , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Helices at a 2-way junction can therefore remain collinear even though no significant electrostatic repulsions exist between them. Moreover, at a 3-helix junction, the collinearity of two helices due to coaxial stacking implicitly means that a plane is formed with the third (Kim et al 2002;Mikulecky et al 2004;Mohanty et al 2005;Ouellet et al 2010). Some 4-helix junctions have also been shown to have relatively planar structures (Lilley 1998(Lilley , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Both Hardin et al and Cornilescu et al used smFRET to study dynamics of a U4/U6 model di‐RNA . Both groups showed that the 3‐helical junction formed by the RNA was remarkably static with little evidence for dynamics on the millisecond to minute timescale, in agreement with studies of other 3‐helical junction RNAs . Hardin et al went on to propose that while the U4/U6 junction is static, the relative orientation of the U4 5′ stem loop can change upon addition of various U4/U6 di‐snRNP proteins with Prp31 promoting approach of the 5′ stem loop toward U4/U6 stem II and Prp3 and Prp4 promoting an increase in 5′ stem loop/stem II distance (Figure (c)).…”
Section: Single‐molecule Studies Of Spliceosomes In Vitromentioning
confidence: 83%
“…56,78 Both groups showed that the 3-helical junction formed by the RNA was remarkably static with little evidence for dynamics on the millisecond to minute timescale, in agreement with studies of other 3-helical junction RNAs. 79 Hardin et al went on to propose that while the U4/U6 junction is static, the relative orientation of the U4 5 0 stem loop can change upon addition of various U4/U6 di-snRNP proteins with Prp31 promoting approach of the 5 0 stem loop toward U4/U6 stem II and Prp3 and Prp4 promoting an increase in 5 0 stem loop/stem II distance (Figure 3(c)). The exact correlation of smFRET data with U4/U6 structure is unclear: Hardin et al hypothesized that their smFRET data are consistent with coaxial stacking of U4/U6 stem I and stem II along with movement of this 5 0 stem loop.…”
Section: 'mentioning
confidence: 99%
“…We previously studied the structure and folding of this junction ( Fig. 1 B) (19). Analysis of the global structure indicated that in the presence of Mg 2þ ions, this junction adopts a conformation based on the coaxial alignment of the C and E helices, with helix D oriented to generate an acute angle with helix C (19).…”
Section: Introductionmentioning
confidence: 99%